Hollow Metal–Organic‐Framework‐Mediated In Situ Architecture of Copper Dendrites for Enhanced CO2 Electroreduction. Issue 23 (6th April 2020) - Zhu, Qinggong; Yang, Dexin; Liu, Huizhen; Sun, Xiaofu; Chen, Chunjun; Bi, Jiahui; Liu, Jiyuan; Wu, Haihong; Han, Buxing
Abstract: Electrocatalytic reduction of CO2 to a single product at high current densities and efficiencies remains a challenge. However, the conventional electrode preparation methods, such as drop‐casting, usually suffer from low intrinsic activity. Herein, we report a synthesis strategy for preparing heterogeneous electrocatalyst composed of 3D hierarchical Cu dendrites that derived from an in situ electrosynthesized hollow copper metal–organic framework (MOF), for which the preparation of the Cu‐MOF film took only 5 min. The synthesis strategy preferentially exposes active sites, which favor's the reduction of CO2 to formate. The current density could be as high as 102.1 mA cm −2 with a selectivity of 98.2 % in ionic‐liquid‐based electrolyte and a commonly used H‐type cell. Abstract : The right dendrites : Electrodeposited hollow metal–organic‐framework‐mediated in situ synthesis of copper dendrites with abundant active sites leads to outstanding performance for electroreduction of CO2 to formate. The current density could be as high as 102.1 mA cm −2 with a selectivity of 98.2 % in ionic‐liquid‐based electrolyte and a commonly used H‐type cell.